2014
DOI: 10.1111/cea.12427
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict allergen‐induced asthma in patients with allergic rhinitis?

Abstract: There is a considerable discordance between reported asthma signs and diagnosed disease by BAP. Simple measurement of allergen-specific IgE for grass pollen was the best predictor of allergen-induced asthma in patients with AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
1
11
1
2
Order By: Relevance
“…Thus, the level of specific serum IgE seems to be important for predicting significant bronchial obstruction after BAP. This strong relationship was also found in patients with grass pollen AR . In contrast, no correlation was found for the Lebel score and the specific IgE in our cohort.…”
Section: Discussionsupporting
confidence: 48%
“…Thus, the level of specific serum IgE seems to be important for predicting significant bronchial obstruction after BAP. This strong relationship was also found in patients with grass pollen AR . In contrast, no correlation was found for the Lebel score and the specific IgE in our cohort.…”
Section: Discussionsupporting
confidence: 48%
“…In addition, the diagnosis was partially based on the SPT results which needed to be evaluated, making this parameter inoperative. Other studies indicated that sIgE was a valid predictor for allergen‐induced allergic symptoms. A recent study reported an excellent correlation for the SPT and bronchial provocation, especially for Alt a, in asthmatic subjects, and that a high sIgE concentration against Alt a was an effective predictor for a positive challenge .…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, neither the TH‐2 cytokines nor the transcription factor pattern could replace the diagnostic value of BAP. Sensitization to A fumigatus is therefore initially a laboratory or skin test finding, which together with sIgE to A fumigatus might be a possible justification for BAP as diagnostic test . Future studies may generate data from sufficient patient numbers to determine a certain A fumigatus sIgE cut‐off level for CF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization to A fumigatus is therefore initially a laboratory or skin test finding, which together with sIgE to A fumigatus might be a possible justification for BAP as diagnostic test. 12,46 Future studies may generate data from sufficient patient numbers to determine a cer- However, this study has some limitations. The number of CF patients who underwent BAP was very small.…”
Section: Ta B L E 3 Mrna Expression Changes In Sputum Cellsmentioning
confidence: 99%